Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

cos 6 a-sin 6 a=cos2a(1-1/4sin 2 2a)

cos6a-sin6a=cos2a(1-1/4sin22a)

Grade:11

1 Answers

Nishant Vora IIT Patna
askIITians Faculty 2467 Points
6 years ago
(cos2a)3 – (sin2a)3
= (cos2a – sin2a )(cos4a + sin4a + cos2a*sin2a)
= (cos2a)(1 – 2 cos2a*sin2a + cos2a*sin2a)
= (cos2a)(1 – cos2a*sin2a )
= (cos2a)(1 – 4cos2a*sin2a/4 )
= cos2a(1-1/4sin22a)

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free